2014
DOI: 10.1002/ejic.201402597
|View full text |Cite
|
Sign up to set email alerts
|

Sila‐α‐galbanone and Analogues: Synthesis and Olfactory Characterization of Silicon‐Containing Derivatives of the Galbanum Odorant α‐Galbanone

Abstract: Silicon compounds 1b–3b are sila‐analogues of the galbanum odorants α‐galbanone (1a), α‐spirogalbanone (2a), and nor‐α‐galbanone (3a), respectively. Sila‐α‐galbanone (1b), sila‐α‐spirogalbanone (2b), and sila‐nor‐α‐galbanone (3b) were synthesized in multistep syntheses in isomerically pure form, starting from Me2SiCl2, (CH2=CH)2SiCl2, and Me2(CH2=CH)SiCl, respectively. Hydroformylation of vinylsilanes, followed by either ring‐closing aldol condensation or ring‐closing alkene metathesis, were the key steps in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 114 diphenyl propargyl alcohol (734), which forms via conversion of the allenylidene intermediate (906) to the acyl complex (907) using water generated in the first step followed by decarbonylation. The iridium carbene complex 924 (Scheme 75) was prepared through treatment of iridium complex 922 with alkyne 923 [1038].…”
Section: Page 114 Of 218mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 114 diphenyl propargyl alcohol (734), which forms via conversion of the allenylidene intermediate (906) to the acyl complex (907) using water generated in the first step followed by decarbonylation. The iridium carbene complex 924 (Scheme 75) was prepared through treatment of iridium complex 922 with alkyne 923 [1038].…”
Section: Page 114 Of 218mentioning
confidence: 99%
“…Besides carbocycles, olefin metathesis can also be used for the construction of other types of rings, using substrates with heteroatom-containing tethers. In 2014, Tacke, Kraft et al reported a Si -heterocyclic fragrance with an intense fruity-green odor and an impressive odor threshold of 0.085 ng/L air, which was the lowest achieved among all the sila-odorants at that time [ 88 ]. The five-membered silacycle was constructed via RCM using the Zhan catalyst, while, formerly, Rh-catalyzed hydroformylation was another key step for simultaneously increasing the carbon chain and introducing a functional group ( Scheme 6 b).…”
Section: Synthesis Of Fragrances Via Ring-closing Metathesismentioning
confidence: 99%
“…Beyond a few exceptional examples on small rings (damascone and galbanone derivatives) [586,587], the RCM has found more application in the synthesis of macrocyclic musky odorants.…”
Section: Metathesismentioning
confidence: 99%
“…Beyond a few exceptional examples on small rings (damascone and galbanone derivatives) [ 586 587 ], the RCM has found more application in the synthesis of macrocyclic musky odorants. Starting from the natural civettone ( 679 ), muscone ( 680 ), and omega-pentadecalactone ( 681 ), numerous medium size macrocycles have been developed and are now commercially available ( Scheme 162 ).…”
Section: Reviewmentioning
confidence: 99%